Pengaruh Variasi Kecepatan Sepeda Motor Listrik Terhadap Konsumsi Daya Baterai - Ananta Maha Putra, I Gusti Ngurah Agung; Septiadi, Wayan Nata; Bandem Adnyana, I Wayan (Teknik Desain Mekanika; Vol 12 No 4 (2023): Oktober 2023 : Teknik Desain Mekanika, 2023)
Abstract Simple magnito electric motorcycle is an alternative means of transportation that uses electricity as a substitute for fossil fuels. This electric motorcycle is expected to provide an overview of the performance of increasing electric power consumption against speed and gravity. Electric power consumption is carried out through testing on electric motorbikes with variations in speed of 20 km/h, 30 km/h and 40 km/h as well as variations in gravity. The distance covered in this test is 1.8 km assuming a flat road. From these tests, the results obtained were that variations in speed and gravity had a significant effect on increasing the consumption of electric power on electric motorcycles. Keywords: Electric Motorcycles, Electric Power Consumption